2017
DOI: 10.1128/aem.00603-17
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Streptomyces coelicolor Carbonyl Reductase for Efficient Atorvastatin Precursor Synthesis

Abstract: Streptomyces coelicolor CR1 (ScCR1) has been shown to be a promising biocatalyst for the synthesis of an atorvastatin precursor, ethyl-(S)-4-chloro-3-hydroxybutyrate [(S)-CHBE]. However, limitations of ScCR1 observed for practical application include low activity and poor stability. In this work, protein engineering was employed to improve the catalytic efficiency and stability of ScCR1. First, the crystal structure of ScCR1 complexed with NADH and cosubstrate 2-propanol was solved, and the specific activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…For the substrate COBE, we observed that the K m value of SmADH31 was only 0.42 mM, which was lower than that of other ADHs including ChADH (7.5 mM) and ScADH (0.59 mM). 21,22 The SmADH31 k cat /K m value for COBE was 5.5 × 10 2 mM −1 s −1 , which was higher than that of ChADH (26.8 mM −1 s −1 ) and ScADH (34.7 mM −1 s −1 ). All these results indicate that SmADH31 possesses a strong binding affinity and high catalytic efficiency for COBE.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…For the substrate COBE, we observed that the K m value of SmADH31 was only 0.42 mM, which was lower than that of other ADHs including ChADH (7.5 mM) and ScADH (0.59 mM). 21,22 The SmADH31 k cat /K m value for COBE was 5.5 × 10 2 mM −1 s −1 , which was higher than that of ChADH (26.8 mM −1 s −1 ) and ScADH (34.7 mM −1 s −1 ). All these results indicate that SmADH31 possesses a strong binding affinity and high catalytic efficiency for COBE.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Carbonyl reductase (EC 1.1.1.148) is the most widely used industrial oxidoreductase for catalyzing the biotransformation of the pro‐ketone substrate to the corresponding chiral alcohol with the reduced form of nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) because of its high activity, excellent enantioselectivity and environmentally friendly effect 9‐13 . Cui et al 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbonyl reductase (EC 1.1.1.148) is the most widely used industrial oxidoreductase for catalyzing the biotransformation of the pro-ketone substrate to the corresponding chiral alcohol with the reduced form of nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) because of its high activity, excellent enantioselectivity and environmentally friendly effect. [9][10][11][12][13] Cui et al 14 employed two substrate-tolerant carbonyl reductases from Bacillus subtilis and Gluconobacter oxydans to efficiently reduce 2-hydroxy acetophenone to (S)-and (R)-1-phenyl-1,2-ethylene glycol in the biphasic system with a yield of 99% and an e.e. of 99%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, biocatalyst has attracted more and more attention due to its wide range of natural sources, mild reaction conditions, high catalytic efficiency, excellent stereoselectivity, and environmental friendship. 9 Carbonyl reductases (CRs, EC 1.1.1.148) are a type of nicotinamide coenzyme-dependent oxidoreductases which catalyze the reduction of a carbonyl group to the corresponding chiral alcohol, in the present of the reduced form of the cofactor, NAD[P]H. 7,10,11 CRs have been employed as a valuable biocatalyst for ezetimibe synthesis. As early as 1997, it was reported that (S)-ET-5 was synthesized by whole cells of Schizosaccharomyces octosporus (ATCC 2479) and S. octosporus (ATCC 4206) containing CRs with the yields of 33.0 and 34.0%, respectively, and the e.e.…”
Section: Introductionmentioning
confidence: 99%